The knowledge retention after continuing health education among midwives in Indonesia (Medical Journal of Indonesia, 2018)
Background: Amongst the Health Care Professionals, midwife has a strategic role in taking care of both mother and child in contributing to their survival, health, and wellbeing. The retaining midwife’s knowledge and quality of care through training on specific skills is strongly needed. This study aimed to evaluate the knowledge retention among midwives after the provision of digestive health, nutrition, and parenting education sessions at immediate and three months after the education.Methods: A serial pre-post intervention experimental study was conducted from January to July 2016 to evaluate the knowledge before (pre-test), immediate after (post-test), and three months after the provision of three sessions of digestion health, nutrition, and parenting (character building) topics by the experts which covered from several areas in Indonesia. The improvement of the sufficient knowledge proportion time by time was analyzed by using McNemar test.Results: The low immediate response rate (77.2%) and very low response after the 3-month follow-up (26.4%) were revealed during the study. At baseline, less than 50% of the subjects had sufficient knowledge on digestive health, nutrition, and parenting. At immediate after and after three months, there were significant improvements in the proportion of sufficient knowledge in nutrition and parenting topics. However, there was a declining of sufficient knowledge at after 3 months group compared to immediate group.Conclusion: The knowledge retention from the continuing health education among widwives in Indonesia decreased after 3 months.